The civic duty to report an offence as an example of lex imperfecta - Kania, Agnieszka (The Opole Studies in Administration and Law, 2017)
This article focuses on the legal nature of the civic duty to report an offence (Article 304(1) of the Code of Criminal Procedure). Assuming that the solution does not constitute a classic example of lex imperfecta, it is concluded that the breach of its provisions might produce effects only in the sphere of moral judgements. While reflecting on the so-called imperfect norms (norms without sanctions), the analysis concerns not only their legal nature and compliance with the requirements of the principles of legislative technique, but also the possibility of compliance with the current provisions of law being motivated by both an external compulsion and an internal compulsion arising out of the authority of law or persuasive and educational processes. Furthermore, based on the analysis of the civic duty to report an offence in terms of criminal trials, it is concluded that the mechanism does not merely create a regulatory framework for rewarding active civic involvement in crime prevention, but also mandates to count on loyalty of that part of society which has internalized certain norms and values correlating with the requirements of the criminal legislation for the public. It also implicates a need for sanction on criminal law.